2018
DOI: 10.1111/nuf.12249
|View full text |Cite
|
Sign up to set email alerts
|

Student evaluations of teaching (SET): Guidelines for their use

Abstract: Student evaluations of teaching (SET) provide a structured way of collecting feedback from students about the course and teacher's effectiveness. We reviewed literature describing use of SET across a broad range of disciplines in undergraduate and graduate education to provide guidelines for faculty in using SET in a nursing or other health professions program. On SET tools, students typically rate their satisfaction with a course and perceptions about the quality of the teaching. It is important to evaluate S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…Some researchers suggested that the evaluation time should depend upon the purpose of evaluations of teaching—teaching improvement or administrative decision making (McKeachie, 1997; Oermann et al, 2018). Wolfer and Johnson (2003) argued that, for the purpose of teaching improvement, the evaluation of teaching should be conducted during the semester or even at the beginning of the semester, because teaching improvement needs sufficient time, and evaluating at the end of the semester cannot help teachers to make adjustments in time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers suggested that the evaluation time should depend upon the purpose of evaluations of teaching—teaching improvement or administrative decision making (McKeachie, 1997; Oermann et al, 2018). Wolfer and Johnson (2003) argued that, for the purpose of teaching improvement, the evaluation of teaching should be conducted during the semester or even at the beginning of the semester, because teaching improvement needs sufficient time, and evaluating at the end of the semester cannot help teachers to make adjustments in time.…”
Section: Discussionmentioning
confidence: 99%
“…This means that, in terms of dependability, when the number of students exceeds a certain value, the impact of the student number will be less obvious. It is unknown whether small classes tend to provide more positive evaluations than large classes (Chang and Hocevar, 2000; Wolfer and Johnson, 2003; Oermann et al, 2018). Future studies should consider the class size as a condition in assessing teachers' teaching quality rated by students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other schools of thought have also argued against the position of those who have little trust for students' evaluation and have indicated that students are capable of accurately evaluating the quality of their learning experiences, courses and/or instruction (Hativa 2013;Benton and Ryalls 2016;Oermann et al 2018). They further argue that contextual indicators, like poorly designed items, unfavourable occasion and students' perception of lecturers, which might result in inconsistent ratings and thus, when these factors are addressed, students will provide quality data.…”
Section: Introductionmentioning
confidence: 99%
“…Course evaluations can be used for curriculum improvement, identifying student needs, and monitoring instructor or program success (Cronbach, ; Spooren et al, ; Oermann et al, ). These evaluations, therefore, have the potential to improve the student learning experience (Lam, ).…”
Section: Introductionmentioning
confidence: 99%